2021
DOI: 10.46602/jcsn.v46i2.610
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis on the Phytochemical, Proximate and Mineral Composition of the Seeds and Peels of Lime

Abstract: Comparative Analysis on the Phytochemical, proximate and mineral composition of the seeds and peels of lime was carried out. The phytochemical, and proximate screenings were carried out using standard methods. The mineral analysis was carried out by using Atomic Absorption Spectrophotometer. The proximate analysis revealed that the seeds contain Moisture 8.20%, Ash 12.09%,Crude fat 8.50%,Crude Protein 1.93%,Crude fibre 20.71%, and Carbohydrate 48.58% while the peels contain Moisture10.60%, Ash 15.27%, Crude fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
0
3
1
Order By: Relevance
“…Fibre also lowers cholesterol levels and prevent plague formation in the blood vessels by improving the absorption and re-absorption of cholesterol and bile acids (Edem et al, 2019;Erhirhie and Ekene, 2013). Value obtained for ether extract (7.70 %) was higher than the value range (2.02 -3.10 %) reported by Bahru et al (2019) and Uzama et al (2015). The carbohydrate content of avocado seed (60.36 %) was higher than that (56.70) reported by Ejimofor et al (2023).…”
Section: Resultscontrasting
confidence: 56%
“…Fibre also lowers cholesterol levels and prevent plague formation in the blood vessels by improving the absorption and re-absorption of cholesterol and bile acids (Edem et al, 2019;Erhirhie and Ekene, 2013). Value obtained for ether extract (7.70 %) was higher than the value range (2.02 -3.10 %) reported by Bahru et al (2019) and Uzama et al (2015). The carbohydrate content of avocado seed (60.36 %) was higher than that (56.70) reported by Ejimofor et al (2023).…”
Section: Resultscontrasting
confidence: 56%
“…Further, they compared the effect of different debittering methods on the proximate composition of orange seeds and reported that boiling for 40 minutes was an optimum tool for obtaining the best quality powder. In a related study by Uzama et al [36], the results for the proximate composition of orange seeds showed that the seeds contain moisture (10.92%), ash (4.31%), crude fat (6.37%), crude fiber (1.67%), crude protein (2.36%), and carbohydrate (74.37%). This variation in the results might be due to the difference in orange varieties selected and pretreatments of the orange seeds, and both of these factors cause highly significant effect on the chemical composition of flours.…”
Section: Resultsmentioning
confidence: 93%
“…Findings of Suteu et al [13] were useful in explaining the current outcomes regarding the mineral contents of orange seed powder, as that study presented similar findings. Results for the mineral composition of orange seeds reported in a related study by Uzama et al [36] showed that the orange seeds contain Mn (0.13 mg/100 g), Cu (0.27 mg/100 g), Zn (0.63 mg/ 100 g), Ca (31.00 mg/100 g), Mg (1.02 mg/100 g), Na (55.56 mg/100 g), and K (57.50 mg/100 g), and these lower values of minerals than our findings might be due to the difference in cultivar, environment, soil conditions, pretreatments, and determining techniques. Current study results were far higher than those El-Safy et al [39] obtained when they looked at the nutritional profile of orange seed flours, as seed flour samples had sizable levels of P, Ca, Mg, K, Cu, Fe, and Zn, making them potentials for future dietary supplements, according to the results, which showed that the analyzed seed flours were thought to be major new mineral sources.…”
Section: Mineral Composition Of Wheat Flour and Orange Seedmentioning
confidence: 86%
“…For instance, the environmental nuisance caused by discarding the seeds results in the release of greenhouse gases and also, huge economic losses to the food industries (Papargyropoulou et al, 2014;Adubofuor et al, 2021). The seeds (constituting about 38% of the weight of the fruit) contain crude fat (6.37%), ash (4.31%), crude protein (2.36%), crude fibre (1.67%), moisture (10.92%) and carbohydrate (74.37%) (Uzama et al, 2021). Contrary to the popular perception that orange seeds are of low economic value, published literatures have enumerated their rich bioactive and nutritional properties such as essential fatty acids, phytosterols, flavonoids, phenols, carotenoids, tannins, saponins, tocopherols, fibers, minerals, and vitamins (Malacrida et al, 2012;El-Safy et al, 2012;Reazai et al, 2014;Farag et al, 2020;Adubofuor et al, 2021;Uzama et al, 2021;Zayed et al, 2021;Moser et al, 2023).…”
Section: Introductionmentioning
confidence: 99%